Linking perceptions of organizational support to temporary agency workers’ well-being - Lopes, Sílvia (2021)
Purpose – This research focused on agency work. Previous studies highlighted the importance of motivations to understand workers’ attitudes, behaviors and well-being. Thus, the purpose of this paper is to analyze the contribution of perceptions of support from organizations to autonomous motivation for temporary agency employment, the relationship of motivations with workers’ well-being and the mediating role ofmotivations between perceptions of organizational support (POS) and workers’ well-being. Design/methodology/approach – The hypotheses were tested with a sample of 3,983 temporary agency workers and using structural equation modeling. Findings – The authors verified that POS from the agency contributed to both autonomous motivation and controlled motivation for temporary agency employment, whereas POS from the client company only contributed to autonomous motivation for temporary agency employment. Moreover, autonomous motivation for temporary agency employment was positively associated with workers’ well-being. Contrary to expectations, controlled motivation for temporary agency employment was not significantly associated with workers’ well-being. As predicted, autonomous motivation for temporary agency employment was a mediator in the relationship between POS and workers’ well-being. Research limitations/implications – The study relies on self-reported data, and it does not have a longitudinal design. Practical implications – An important implication of this research study is that organizations, through the support provided to the workers, may contribute positively to increase workers’ autonomous motivation for temporary agency employment, and, in turn, more autonomous motivation for temporary agency employment relates to higher levels of workers’ well-being. Originality/value – The study innovates by including in the same model variables that may contribute to workers’ motivation for temporary agency employment as well as the outcomes that may arise from workers’ motivation for temporary agency employment.